2017
DOI: 10.20431/2454-8685.0304002
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and Monitoring of Land Surface Temperature, Urban Heat Island with Land use-land cover of Dhaka City using Satellite imageries

Abstract: Dhaka city has been expanding rapidly by urbanization process to meet up the needs for increasing population in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Previous literature on LULC changes and LST was helpful to conduct the study and to compare the outcome of this study. The increasing trend of built-up and bare lands and decreasing trend of vegetation and water bodies have been found in this research, which is consistent with previous studies (Ahmed et al 2013;Dewan and Yamaguchi 2009;Mia et al 2017). Ahmed et al (2013) reported that the urban area increased from 15.68 to 36.91% while vegetation decreased from 19.97 to 8.53% in Dhaka city since 1989-2009.…”
Section: Discussionsupporting
confidence: 92%
“…Previous literature on LULC changes and LST was helpful to conduct the study and to compare the outcome of this study. The increasing trend of built-up and bare lands and decreasing trend of vegetation and water bodies have been found in this research, which is consistent with previous studies (Ahmed et al 2013;Dewan and Yamaguchi 2009;Mia et al 2017). Ahmed et al (2013) reported that the urban area increased from 15.68 to 36.91% while vegetation decreased from 19.97 to 8.53% in Dhaka city since 1989-2009.…”
Section: Discussionsupporting
confidence: 92%
“…Dhaka (11.7%) and Karachi (3.2%) demonstrated relatively small percentages of green spaces. Dhaka's green spaces have been continuously decreasing due to the rapid urban development [34], which has also resulted in increasing the LST levels and the UHI [87,88].…”
Section: Spatial Patterns Of Lulcmentioning
confidence: 99%
“…Decreasing urban green spaces: Past studies have shown that rapid urban development caused a decline in the green spaces in all four cities, namely, Colombo [81], Mumbai [17], Karachi [94], and Dhaka [87]. The green spaces of all four cities are becoming more vulnerable to conversion into built-up lands in the future.…”
Section: Urbanization Related Issues and Future Challengesmentioning
confidence: 99%
“…al., 2015;Weier & Herring, 2000). The skin temperature of the earth surface, which can be measured from ground and satellite data, have great influence on physical, biological and chemical process like heat and energy exchange between the surface and the atmosphere, can be demarcated as land surface temperature (LST) (Mia, Bhattacharya & Woobaidullah, 2017;Paruelo, Epstein, Lauenroth & Burke, 1997). Song et al, (2018) have featured other studies to analyze the relationship between the LST and NDVI.…”
Section: Introductionmentioning
confidence: 99%
“…For instances, the first group of studies examined the role of geospatial tools in broad perspective (Anandababu, Purushothaman & Suresh Babu, 2018;Avdan & Jovanoska, 2016;Grover & Singh, 2015;Guha & Govil, 2020;Li et al, 2015;Saha, Paul, Gupta & Saha, 2016;Song et al, 2018;Tran et al, 2017). The second group of studies (Islam et al, 2019;Mia et al, 2017;Mondal & Uddin, 2018;Shimu et al, 2019;Uddin & Mondal, 2020) explored the factors that affects the land surface elements in city/regional territory. Very few studies address the monitoring issues from very micro unit often in ward boundary setting.…”
Section: Introductionmentioning
confidence: 99%